Implementation of the Project Citizen Model in Pancasila Education learning as an Effort to Optimize the Improvement of Independent Character and Creative Thinking Skills in Elementary Schools - Fatchur Rahman Taufiq; Alif Mudiono; Intan Sari Rufiana (Didaktika: Jurnal Kependidikan, 2025)
This study aims to analyze the implementation of the Project Citizen learning model in the Pancasila Education subject at SDN 1 Banyuurip as an effort to optimize the improvement of independent character and creative thinking skills of grade 5 students. Education in the 21st century requires students to have relevant skills, including critical thinking, creativity, and having an independent character. Based on initial observations, it was found that students tend to be passive and are not used to expressing opinions or completing tasks independently. The Project Citizen model is implemented through a series of steps such as problem identification, problem selection, information collection, portfolio creation, and reflection. This study uses a qualitative descriptive approach with data collection methods in the form of observation, interviews, and questionnaires. The results of the study showed that the implementation of the Project Citizen model consistently improved the quality of learning, as seen from the increase in the learning implementation score from the category of "good" to "very good." This model also has a positive impact on developing students' initiative, self-confidence, and discipline, and encouraging them to think creatively in solving problems relevant to everyday life. The conclusion of this study shows that the Project Citizen model is effective in forming independent character and improving creative thinking skills, so that it can be adopted as an innovative learning model in Pancasila Education in elementary schools.